Percutaneous Endoscopic Gastrostomy with Jejunal Extension for an Encapsulating Peritoneal Sclerosis Refractory to Surgical Enterolysis. Issue 5 (September 2016) - Banshodani, Masataka; Kawanishi, Hideki; Moriishi, Misaki; Shintaku, Sadanori; Hashimoto, Shinji; Tsuchiya, Shinichiro
Surgical enterolysis is the final option for patients with encapsulating peritoneal sclerosis (EPS). However, EPS is sometimes refractory to surgical enterolysis. This is the first report of successful use of percutaneous endoscopic gastrostomy with jejunal extension (PEG-J) in a patient with EPS that was refractory to surgical enterolysis. We propose that sustained drainage of digestive juices by PEG-J, along with central venous nourishment at home, can be a treatment option for patients with EPS that cannot be treated with radical measures.